Evaluation of Antioxidant and Antihyperlipidemic Activity of extracts Rich in Polyphenols - Shetgiri P.P,; Darji. K.K,; D’Mello P.M, (International Journal of Phytomedicine, 2010)
Polyphenols are phytochemicals present in plants that contribute to their antioxidant and different pharmacological activities. Flavonoids comprise of one class of polyphenols which play a beneficial role in preventing free radical damage and owe its antioxidant property. Lipid peroxidation and lipid-derived oxidized products have been implicated in the pathogenesis of a variety of human diseases. To clarify the role of oxidative stress in prevention of atherosclerosis and hypercholesterolemia, the antioxidant status of plant extracts of Oroxylum indicum, Vitis vinifera and Policosanol isolated from, Saccharum officinarum were selected for the study. The extracts were evaluated by in vitro methods by monitoring the production of malondialdehyde as Thiobarbituric acid Reacting Substances (TBARs). The antihypperlipidemic activity was examined in cholesterol induced hyperlipidemic model using Albino Wistar rats. The result of the study exhibited significant reduction in total cholesterol, triglycerides, LDL-C, VLDL-C levels and remarkable increase in the level of HDL-C when compared to standard lovastatin drug. The artherogenic index and LDL-C: HDL-C risk ratio was also reduced to significant extent in the group treated with extracts. The levels of SGOT and SGPT were estimated and found to be significantly less than that of hyperlipidemic control group. The highest antihyperlipidemic activity was exhibited by total extract of the bark of Oroxylum indicum followed by extracts of fruits of Vitis vinifera and Policosanol isolated from sugarcane wax.